Community support that's more than a sticking plaster. (5th January 2021) - Feinmann, Jane
Abstract : The BMJ 's appeal this year supports the Independent Food Aid Network, a charity that has helped independent food banks and other community meal providers throughout the covid-19 pandemic, writes Jane Feinmann